1999
DOI: 10.1021/ja991100b
|View full text |Cite
|
Sign up to set email alerts
|

Variable Pore Size, Variable Chemical Functionality, and an Example of Reactivity within Porous Phenylacetylene Silver Salts

Abstract: Investigations on molecular variants of the 3-fold symmetric 1,3,5-tris(4-ethynylbenzonitrile)benzene crystallized with silver triflate revealed a nearly invariant pseudohexagonal porous structure type. Modifications involved the attachment of pendant groups to the central aromatic ring of the parent molecule. Pendant groups include the vinyl group, stilbene, the chiral group myrtanol, and groups with different chemical functionalities such as alcohols, ethers, and esters. Modifications also included the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
158
0
3

Year Published

2000
2000
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 223 publications
(163 citation statements)
references
References 80 publications
2
158
0
3
Order By: Relevance
“…In particular, coordination complexes are interesting not only for the structural aspects but also for their intriguing functional properties, which one may exploit in the fields of catalysis, magnetism, and optical applications. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The promise of these construction strategies for creating functional materials has already been demonstrated for different applications, such as second harmonic generation, 15,16 gas storage, including sizeselective sorption and molecular recognition, [17][18][19][20] and catalysis, [21][22][23][24] as well as applications to magnetic materials. 8,[25][26][27] The coordination interaction has also been employed to construct supramolecular architectures at surfaces, offering the possibility to design low-dimensional organic-inorganic hybrid materials.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, coordination complexes are interesting not only for the structural aspects but also for their intriguing functional properties, which one may exploit in the fields of catalysis, magnetism, and optical applications. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The promise of these construction strategies for creating functional materials has already been demonstrated for different applications, such as second harmonic generation, 15,16 gas storage, including sizeselective sorption and molecular recognition, [17][18][19][20] and catalysis, [21][22][23][24] as well as applications to magnetic materials. 8,[25][26][27] The coordination interaction has also been employed to construct supramolecular architectures at surfaces, offering the possibility to design low-dimensional organic-inorganic hybrid materials.…”
Section: Introductionmentioning
confidence: 99%
“…[12,15] We have found that phenylacetylene molecules with three capping nitrile groups radially pointing out from the core of the molecule engender in the coordinating silver ions a similar trigonal planar geometry. Examples of such nitriles are given in Figure 2.…”
Section: Hexagonal-porous Solids From Phenylacetylene Nitrilesmentioning
confidence: 92%
“…To wit, we can introduce guests into the hexagonal columnar pores which will react with the channel walls and ultimately strengthen these walls. For example, we recently reported [12] that acid anhydrides can react in an alcohol derivatized hexagonal porous channel to form esters without loss of crystallinity, as evidenced by X-ray powder data. In this work we prepared a phenylacetylene nitrile whose alcohol groups dangle into the honeycomb pores.…”
Section: Pore Functionalizationmentioning
confidence: 99%
See 2 more Smart Citations